Causes and Effects of Variation Orders in the Construction of Terrace Housing Projects: A Case Study in the State of Selangor, Malaysia - Noraziah Mohammad; Adi Irfan Che Ani; Riza Atiq O.K. Rakmat (International Journal of Supply Chain Management, 2017)
This paper investigates the most significant causes and effects contribute to the variation orders in the construction of housing projects in the States of Selangor Malaysia. Data was collected based on the existing literature reviews and also contract documents from a total of 61 housing project located at nine district in the state of Selangor. The data were analysed and the formulate the findings. The result from revealed four most significant causes variation orders which are: Change of scope by owner, Substitution of materials by owner, Changes of specification by owner and Changes of design by consultant. Meanwhile the effects of the variation orders are time and cost overrun. The finding concludes that owner is the major source of the variation orders in construction of building projects and suggested that owner should have adequate planning and recourses before initiating a project in order to avoid variation order during the construction stage.